Model Konseling Berbasis Iman dalam Pemulihan Krisis Afeksi Remaja Korban Broken Home - Muhammad Ferdiansyah; Nur Hasanah Harahap (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2023)
The purpose of this study is to offer a counseling model for crisis recovery for adolescent victims of Broken Home. This type of research is qualitative research with a grounded theory approach. Data collection techniques using observational instruments, interviews, and documentation. Validity checks use four criteria, namely (1) Trust test, (2) Transferability test, (3) Defendability test, and (4) Conformity test. Furthermore, data analysis was carried out with four stages, namely (1) open coding, (2) axial coding, (3) selective coding, and (4) theoretical note. The results of the study resulted in a model of faith-based counseling. The faith base highlighted by this model is the main advantage, making it effective in guidance and counseling services in Indonesia. The focus of therapy in faith-based counseling is to restore a sense of security in counseling by touching on self-confidence in broken-home adolescents so that it can become a vehicle for developing a variety of potential excellence for adolescents in navigating the dynamics of life. Guidance and counseling are also responsible for creating a sense of security in adolescent victims of broken homes or counseling in changing the way of thinking, behaving, and living culture. Security and affection become the ideal life of humans at the level of personal, family, and community life.